Multimodality imaging evaluation before transcatheter aortic valve implantation: incidence of contrast medium-induced acute kidney injury, risk factors and prognosis. Issue 5 (May 2018) - Schneider, C.; Brumberg, A.; Roller, F.C.; Rixe, J.; Roth, P.; Krombach, G.A.
Abstract : Aim: To evaluate the incidence, risk factors, and prognostic implications of contrast medium-induced acute kidney injury (CI-AKI) in patients undergoing transcatheter aortic valve implantation (TAVI) evaluation. Materials and methods: Datasets from 98 out of 207 consecutive patients referred for multidetector computed tomography (MDCT) for TAVI evaluation were eligible for evaluation and were analysed retrospectively. The incidence of CI-AKI was correlated to outcome and to potential risk factors: kidney function (estimated glomerular filtration rate [eGFR]), heart failure, diabetes, amount of contrast medium, and duration of examination period. Results: CI-AKI occurred in 67 patients (68.4%) and mainly correlated with eGFR ( p= 0.01) and the amount of contrast medium as a function of eGFR ( p= 0.04). CI-AKI occurred before TAVI in 36 (53.7%) patients of which 13 (19.4%) did not undergo TAVI. In-hospital all-cause mortality was 21.4%, and of those 21 patients, 18 (85.7%) had CI-AKI and nine (42.9%) did not undergo TAVI. One-year all-cause mortality was 39.8%, and of those 39 patients who died within 1 year, 31 (79.5%) had CI-AKI. Conclusion: CI-AKI mostly occurs already before TAVI as a consequence of pre-procedural imaging, which therefore represents the main contributor for CI-AKI in relation to TAVI. Regarding the observation that some patients will ultimately have no benefit because TAVI is not performed and the poor prognosis linked to CI-AKI should encourage improvement in patient selection when referring to pre-procedural imaging. Highlights: Pre-procedural imaging before TAVI involves a remarkable risk for CI-AKI. In most TAVI candidates, CI-AKI occurs before TAVI during pre-procedural imaging. Pre-existing impaired renal function is the decisive risk factor for CI-AKI. CI-AKI even at a low stage is associated with a higher mortality in TAVI candidates.